Cash Shortage in the Former Soviet Union. (IMF Working Papers; Working Paper ;, 1994)
An unexpected shortage of banknotes emerged during 1992 in the former Soviet Union. The cash shortage is explained by the asymmetry in the monetary union that prevailed, under which one member (the Russian Federation) controlled banknote production while every member could create deposit money. Interest rate rigidity forestalled an equilibrating adjustment in demand for banknotes. The possible efficiency costs of the cash shortage are explored.